Acculturation of consumerism among the Orang Asli community in Jelebu, Negeri Sembilan - Gill, Sarjit S.; Rosnon, Mohd Roslan; Redzuan, Ma'rof (Universiti Putra Malaysia Press, 2010)
This article is based on the research results which were intended to identify consumerism trends among the Orang Asli , particularly with regards to purchase of luxury goods and management of their finances. The concept of consumerism refers to the motivation of an individual to identify himself or herself by means of a product or service, especially one which is commercially branded and denotes status. A total of 215 Orang Asli from five settlements in the district of Jelebu were involved in this study. Gathering of information was done by means of both qualitative and quantitative data collections. These include in-depth interviews and observations along with the simple random survey technique using questionnaires. Research findings show that consumerism among the Orang Asli does not differ much from other mainstream communities. They employ luxury items and services in very much the same way as done by other mainstream communities. From the aspect of financial management, however, they occupy the lowest rungs, and a substantial portion of their income is allocated for the purpose of procuring luxury goods. This is done to such an extent that it denies them the means for other more important and needed purposes. The implication of this research finding is that knowledge and information regarding the utilization and management of finances ought to be assimilated by the Orang Asli community, so that they do not become victims of modern-world hedonism and luxury brought about by the mainstream society.